Influence of religiosity and educational background on marital satisfaction of couples in Oyo State, Nigeria (2013)
The purpose of this study is to investigate the influence of religiosity and educational background on marital satisfaction of couples in Oyo State, Nigeria. Two hundred (200) couples constituted the study’s sample that was selected through simple random sampling technique in Oyo State, Nigeria. Both the independent and dependent variables were measured with standardized instruments (a self developed scale tagged marital satisfaction Questionnaire was used) with 0.81 reliability coefficient and the data obtained was analyzed using Pearson Product Moment Correlation (PPMC). Two research questions were formulated and answered. The result shows that there is a significant relationship between religiosity and marital satisfaction among selected couples (r= .771; P<0.05) and there is a significant relationship between educational background and marital satisfaction of selected couples (r= .771; P<0.05). In view of these findings, the study stresses and advocates the need for family counselling centres to be established and be functional in various communities, and couples should be taught the importance of attending and visiting family counseling centers. Marriage seminars and workshops should be introduced to encourage marriage counsellors, religious bodies and other stake holders of family affairs to educate married couples and also the mature singles so as to will help them to re-orientate their knowledge for efficient marriage life ahead.